Comparison of optical feedback dynamics of InAs/GaAs quantum-dot lasers emitting solely on ground or excited states - Lin, Lyu-Chih; Chen, Chih-Ying; Huang, Heming; Arsenijević, Dejan; Bimberg, Dieter; Grillot, Frédéric; Lin, Fan-Yi (Optics letters, 2018)
We experimentally compare the dynamics of InAs/GaAs quantum dot lasers under optical feedback emitting exclusively on ground states (GSs) or excited states (ESs). By varying the feedback parameters and putting focus either on their short or long cavity regions, various periodic and chaotic oscillatory states are found. The GS laser is shown to be more resistant to feedback, benefiting from its strong relaxation oscillation damping. In contrast, the ES laser can easily be driven into complex dynamics. While the GS laser is of importance for the development of isolator-free transmitters, the ES laser is essential for applications taking advantages of chaos.